The potential of mHealth for older adults on dialysis and their care partners: What’s been done and where do we go from here? - Burrows, Brett; DePasquale, Nicole; Ma, Jessica; Bowling, C. Barrett (Frontiers in Nephrology, 2023)
Self-care, or the dynamic, daily process of becoming actively involved in one’s own care, is paramount to manage and prevent complications of end-stage kidney disease. However, many older dialysis patients face distinctive challenges to adequate engagement in self-care. One promising strategy for facilitating self-care among older dialysis patients and their care partners is the utilization of mobile health (mHealth). mHealth encompasses mobile and wireless communication devices used to improve healthcare delivery, patient and care partner outcomes, and patient care. In other disease populations, mHealth has been linked to maintenance of or improvements in self-management, medication compliance, patient education, and patient-provider communication, all of which can slow disease progression. Although mHealth is considered feasible, acceptable, and clinically useful, this technology has predominately targeted younger patients. Thus, there is a need to develop mHealth for older dialysis patients and their care partners. In this article, we describe current mHealth usage in older dialysis patients, including promising findings, challenges, and research gaps. Given the lack of research on mHealth among care partners of older dialysis patients, we highlight lessons learned from other disease populations to inform future design and implementation of mHealth for these key stakeholders. We also propose that leveraging care partners represents an opportunity to meaningfully tailor mHealth applications and, by extension, improve care partner mental and physical health and decrease caregiver burden. We conclude with a summary of future directions to help older dialysis patients and their care partners receive recognition as target end-users amid the constant evolution of mHealth.